Theory of Religion and Historical Research. A Critical Realist Perspective on the Study of Religion as an Empirical Discipline - Seiwert, Hubert (Zeitschrift für Religionswissenschaft, 2020)
The article discusses the connection between theory formation and historical research in the study of religion. It presupposes that the study of religion is conceived of as an empirical discipline. The empirical basis of theories is provided primarily by historical research, including research in the very recent past, that is, the present time. Research in the history of religions, therefore, is an indispensable part of the study of religion. However, in recent discussions on the methods, aims, and theoretical presuppositions of the discipline, research in the history of religions largely is ignored. To shed some light on this blind spot, the article builds on the philosophy of science of Critical Realism. While the first part deals with the role of historical research in theoretical discourses of the discipline, the second part explains fundamental ontological and epistemological positions of Critical Realism and their implications for empirical research. On this basis, some methodological problems of theory formation in the study of religion are discussed in the third part. In particular, it is argued that it is impossible to validate empirically theories of religion that aim to explain what religion is. The concluding part sketches ways of theory formation in the study of religion that does not take religion as the explanandum but as the theoretical perspective that guides research.